UPTAKE Pb LIMBAH CAIR INDUSTRI KERTAS OLEH LELE DUMBO (Clarias gariepenus) DAN ECENG GONDOK (Eichornia crassipes) - Sri Yulina Wulandari (Buletin Oseanografi Marina, 2011)
Abstract The aims of this research was to study accumulation rate of Pb in both King Cat Fishes (Clarias gariepenus) and waterhyacinth (Eichornia crassipes), so was decreasing rate of Pb in waste water of pulp and paper industry. This research was experimental laboratorism. Eighteenth glass wessel were filled 10 litres the mixture of pulp and paper waste water and fresh water whereas  40% volume of pulp and paper waste water. The result sowed that Pb heavy metal content in both King Cat Fishes and waterhyacinths increased by  time treatment. Pb content in head of fishes was greater by aeration than that in body of fishes without aeration. Pb content in waterhyacinths was greater by aeration than that without aeration. Pb content in waste water decreased by time  treatment. The decreasing rate of Pb in waste water was greater by aeratin than that without aeration.   Key words: Uptake Pb, waste water, pulp and paper industry, King Cat  Fish, waterhyacinth